Bilateral agreement for academic years 2008/2013 Lifelong Learning Programme: Higher Education (Erasmus) between Universidades Lusíada de Lisboa-Porto-Vila Nova de Famalicão and Technische Universität Berlin - Universidades Lusíada de Lisboa (2015)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Subject area: Architecture / Urbanism